Child abuse and neglect and mental health outcomes in adulthood by ethnicity: Findings from a 40-year longitudinal study in New Zealand/Aotearoa. - Telfar S; McLeod GFH; Dhakal B; Henderson J; Tanveer S; Broad HET; Woolhouse W; Macfarlane S; Boden JM (Elsevier B.V., 2023)
BACKGROUND: Longitudinal studies consistently report adverse long-term outcomes of childhood maltreatment. Little is known about the impact of childhood maltreatment on mental health among a marginalized population (New Zealand Māori); therefore, we cannot assume the effects of maltreatment are the same across the population. OBJECTIVE: Associations were examined between childhood sexual abuse (CSA), childhood physical punishment (CPP) and childhood neglect (CN) (<16 years) and mental health outcomes 18-40 years, by ethnicity (Māori/non-Māori). PARTICIPANTS AND SETTING: Data from the Christchurch Health and Development Study, a study of a birth cohort of 1265 children born in Christchurch in 1977. By age 40, 17.8 % (n = 191) reported New Zealand Māori ethnic identity; 82.2 % (n = 883) were non-Māori. METHODS: CSA, CPP (<16 years) were measured at 18, 21 years; CN was measured at 40 years. Major depression, anxiety disorder, suicidal ideation, alcohol abuse/dependence and cannabis abuse/dependence were measured at ages 21, 25, 30, 35 and 40 years. Childhood confounding variables controlled. Analyses were extended to include Māori ethnicity. RESULTS: After statistical adjustment, experience of severe childhood maltreatment increased odds of mental health problems 1.8-2.6×, compared to no maltreatment; the effects of maltreatment were similar for males and females. For Māori, some higher rates of mental health problems were seen among those maltreated, no statistically significant associations were detected after Bonferroni correction (among severe maltreatment vs. no maltreatment). Limitations should be considered when interpreting results. CONCLUSIONS: Exposure to childhood maltreatment has long-term effects into middle-age. Further research employing culturally-sensitive approaches may help clarify Māori childhood maltreatment outcomes.
Keywords: Childhood maltreatment; Childhood neglect; Childhood physical abuse; Childhood sexual abuse; Longitudinal study; Mental health; Māori ethnicity; Female; Male; Middle Aged; Humans; Child; Ethnicity; Longitudinal Studies; New Zealand; Child Abuse; Alcoholism; Depressive Disorder, Major; Outcome Assessment, Health Care